(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2016)
General anesthesia is of course valued for sparing patients the physical pain and psychological trauma of being sensate and conscious during surgery, but it also poses a specific challenge to the narrative continuity often seen as a defining aspect of human identity and of mental health. The patient is (arguably) absented from the scene in which his or her body is (arguably) traumatized, and then returns to awareness to find a body that has been changed. This rupture in continuity presents a challenge to coherent first-person narration. Examining some of the strategies used by writers to represent the gap opened up by anesthesia, I suggest that such accounts illuminate our understanding of the connections between narrative rupture, trauma, and an ethical responsibility to recognize the possibility of sentience, and hence the capacity for suffering, in anaesthetized patients.